2017
DOI: 10.1007/s10792-016-0434-x
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in patterns of uveitis at a tertiary referral center in Northern Italy: analysis of 990 consecutive cases

Abstract: PurposeThe role of uveitis, an uncommon ocular disease, is often neglected in research and treatment of autoimmune conditions. The study described the spectrum of uveitis at a referral center in North Italy, and compared that to a previously published series of patients.MethodsWe reviewed all patients with uveitis diagnosed from 2013 to 2015 at the Immunology Eye Unit, Arcispedale S. M. Nuova-IRCCS, Reggio Emilia, Italy. We examined patient characteristics, disease spectrum, and etiologies.ResultsIn total, 990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 56 publications
6
30
1
2
Order By: Relevance
“…Using the Medline database, a review of the literature was performed from 1976–2017 that reported observational data from patients with uveitis in Europe, using the following terms for the literature search: ‘uveitis,’ ‘pattern of uveitis,’ ‘uveitis in Europe,’ and ‘epidemiology of uveitis.’ Twenty-four articles published in the years 1976–2017, reporting uveitis in 24,126 patients in Europe were identified [19–43]. The records of patients referred to the Department of Ophthalmology and the literature data were analyzed in terms of gender, age, and major causes of uveitis, to identify similarities and differences.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Medline database, a review of the literature was performed from 1976–2017 that reported observational data from patients with uveitis in Europe, using the following terms for the literature search: ‘uveitis,’ ‘pattern of uveitis,’ ‘uveitis in Europe,’ and ‘epidemiology of uveitis.’ Twenty-four articles published in the years 1976–2017, reporting uveitis in 24,126 patients in Europe were identified [19–43]. The records of patients referred to the Department of Ophthalmology and the literature data were analyzed in terms of gender, age, and major causes of uveitis, to identify similarities and differences.…”
Section: Methodsmentioning
confidence: 99%
“…1 Tuberculosis (TB) has historically been considered a major cause of uveitis, but the importance of TB as a primary cause of uveitis has gradually decreased in the last decades, although it has recently re-emerged. [2][3][4] TB is an infectious disease caused by Mycobacterium tuberculosis. One-third of the world's population is thought to be infected with M. tuberculosis and in 2015, 10.4 million new infections occured.…”
Section: Introductionmentioning
confidence: 99%
“…Of 980 consecutive patients at the All India Institute of Medical Sciences from 2011 to 2013, 131 (13.36%) had intermediate uveitis [16]. In contrast, prevalence of intermediate uveitis was 5.5% of 990 patients in Northern Italy from 2013 to 2015 [17]. Miserocchi et al reviewed 24 uveitis surveys reporting over 26,000 patients that were published before 2012; the average reported prevalence of intermediate uveitis was 9.5 +/À 5.6% [18].…”
Section: Epidemiology Prevalencementioning
confidence: 99%